Case study of medical evacuation before and after the Fukushima Daiichi nuclear power plant accident in the great east Japan earthquake. Issue 1 (December 2015) - Okumura, Tetsu; Tokuno, Shinichi
Abstract Introduction In Japan, participants in the disaster-specific medical transportation system have received ongoing training since 2002, incorporating lessons learned from the Great Hanshin Earthquake. The Great East Japan Earthquake occurred on March 11, 2011, and the very first disaster-specific medical transport was performed. This article reviews in detail the central government's control and coordination of the disaster medical transportation process following the Great East Japan Earthquake and the Fukushima Daiichi Nuclear Power Plant Accident. Case description In total, 124 patients were air transported under the coordination of the C5 team in the emergency response headquarter of the Japanese Government. C5 includes experts from the Cabinet Office, Cabinet Secretariat, Fire Defense Agency, Ministry of Health, Labour and Welfare, and Ministry of Defense. In the 20–30 km evacuation zone around the Fukushima Daiichi nuclear power plant, 509 bedridden patients were successfully evacuated without any fatalities during transportation. Discussion and evaluation Many lessons have been learned in disaster-specific medical transportation. The national government, local government, police, and fire agencies have made significant progress in their mutual communication and collaboration. Results Fortunately, hospital evacuation from the 20–30 km area was successfully performed with the aid of local emergency physicians and Disaster Medical Assistance Teams (DMATs) who have vast experience in patient transport in the course of day-to-day activities. The emergency procedures that are required during crises are an extension of basic daily procedures that are performed by emergency medical staff and first responders, such as fire fighters, emergency medical technicians, or police officers. Medical facilities including nursing homes should have a plan for long-distance (over 100 km) evacuation, and the plan should be routinely reevaluated with full-scale exercises. In addition, hospital evacuation in disaster settings should be supervised by emergency physicians and be handled by disaster specialists who are accustomed to patient transportation on a daily basis.